Synthesis, characterization and thermal behaviour of solid-state compounds of light trivalent lanthanide succinates - Lima, L. S. [UNESP]; Caires, Flavio J. [UNESP]; Carvalho, C. T. [UNESP]; Siqueira, A. B.; Ionashiro, Massao [UNESP] (Elsevier B.V., 2010)
Characterization, thermal stability and thermal decomposition of light trivalent lanthanide succinates, Ln(2)(C(4)H(4)O(4))(3)center dot nH(2)O (Ln = La to Gd, except Pm) were investigated employing simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), infrared spectroscopy, TG-FTIR system, elemental analysis and complexometry. The dehydration of the lanthanum and cerium compounds occurs in a single step, while for the praseodymium to gadolinium compounds the dehydration occurs in two consecutive steps. The thermal decomposition of the anhydrous compounds occurs in consecutive and/or overlapping steps, except for the cerium compound, with formation of the respective oxides, CeO(2), Pr(6)O(11) and Ln(2)O(3) (Ln = La, Nd to Gd), as final residue. The results also provided information concerning the denticity of the ligand and thermal behaviour of these compounds. (C) 2010 Elsevier BM. All rights reserved.
Keywords: Light trivalent lanthanides; Succinate; Thermal behaviour